Increased-Resistance Phenotype Resulted from Elevated β-Lactamase Enzyme Activity in Salmonella Clinical Isolates - Mercedeh Tajbakhsh; Mohammad Yaghoobi Avini; Jahan Ali Khajeh; Masoud Alebouyeh; Ehsan Nazemalhosseini Mojarad; Mohammad Reza Zali (مجله دانشکده پزشکی اصفهان, 2012)
Background: Beta lactamase enzymes are the most important agents involved in promoting antimicrobial resistance patterns in bacteria. The aim of the present study was to investigate probable roles of enzyme activity divergence in production of different phenotypic resistance patterns among extended-spectrum beta lactamase (ESBL) producing Salmonella clinical isolates. Methods: Detection of ESBLs-related phenotypes was performed by initial screening and specific tests among 174 Salmonella isolates through disk diffusion, and combined disk and minimal inhibitory concentrations (MIC) methods. Polymerase chain reaction (PCR) was used to identify blaTEM, blaCTX, and blaSHV on both chromosomal and plasmid DNA extracts. The enzymatic activity of each isolate was determined by iodometric, biological, and spectrophotometric assays on crude protein extracts in the presence of a specific substrate. Findings: The frequency of ESBL producing isolates was 4%. MIC values for isolates showed differences at higher cephalosporin concentrations. All isolates were negative for blaSHV, but were carriers of blaTEM and blaCTX genes on their plasmids. The enzyme activities on cephalosporins were diverse at constant concentration of protein extracts. Conclusion: Diverse expression levels of ESBLs among beta-lactamase producing isolates could explain their different hydrolytic activities. Probable diversity among beta- lactamase subfamily members, existence and expression of more than one gene, and involvement of other resistant mechanisms can explain resistant phenotype variations in these bacteria. Keywords: Beta-lactamase activity, Salmonella, Antimicrobial resistance